The safety and effectiveness of tDCS for epileptic patients: A systematic review and meta-analysis - Xiao-Tong Ding; Ming-Yu Hu; Chi Wang; Wei-Ye Kang; Jin-Zhao Huang; Rui-Yu Wang; Qiu-Song Shen; Hou-Ming Kan (Complementary Therapies in Medicine)
Background and purpose: Although transcranial direct current stimulation (tDCS) has been used in the treatment of epilepsy for many years, further research is needed on the efficacy and safety of tDCS treatment. This systematic review and meta-analysis aimed to explore the effectiveness of tDCS on seizure frequency (SF), epileptiform discharges, depression, anxiety, and cognitive function in epilepsy. Materials and methods: We searched the Cochrane Library, PubMed, Embase, Scopus, and Web of Science databases from inception to 9 September 2024. The primary outcomes included SF. The secondary outcomes included epileptiform discharges, depression, anxiety, cognitive function, and adverse events. The meta-analysis was conducted using Review Manager 5.4 software. Results: 12 trials were included, 356 participants (219 in the tDCS group and 137 in the sham group). Among the included studies, three were of high risk, two were of some concern, and seven were of low risk. For the primary outcome metrics, tDCS can reduce the frequency of epileptic seizures (SMD = − 0.63, 95 % CI = [-0.90, − 0.36], P < 0.00001). For secondary outcome measures, there are no statistical differences between the tDCS group and the sham group in epileptiform discharges (SMD = − 0.27, 95 % CI = [-0.71, 0.16], P = 0.22) and adverse events (MD = 1.30, 95 % CI = [0.49, 3.45], P = 0.60). The outcomes of tDCS treatment for depression and anxiety were inconsistent. tDCS did not enhance or impair cognitive function. Conclusion: tDCS can reduce SF but has no effect on epileptiform discharges in patients with epilepsy. The current evidence is limited to support tDCS treatment for depression, anxiety, and cognitive function in epilepsy patients. Future studies should be standardized and personalized, ensure higher methodological rigor, and probe long-term effects to prove the findings further.